Energy valorization of Miscanthus x giganteus biomass: A case study in Croatia - Bilandžija Nikola; Jurišić Vanja; Voća Neven; Leto Josip; Matin Ana; Grubor Mateja; Krička Tajana (Journal on Processing and Energy in Agriculture, 2017)
The aim of this study is to determine the calorific values, chemical composition (proximate and ultimate analysis, micro and macro elements) and cell structure (composition of lignocellulose) of Miscanthus x giganteus biomass cultivated in Croatian. Research results represents the average values of biomass (n = 108) cultivated at two locations in Croatia (Bistra, Medvednica), during the three-year research period, three harvest periods (autumn, winter, spring) per year and two fertilizer treatments (N0 i N50). Determined average values of some important parameters are: low calorific value - 17.25 MJ/kg, ash content - 1.49 %, carbon content - 48.75 %, nitrogen content - 0.47 %, sulfur content - 0.07 %, cellulose content - 49.22 % and lignin content - 29.25 %. The obtained results have shown that Miscanthus x giganteus has potential to be a significant source of good quality raw material in the production of solids biofuels.